Improved Functional Outcome in Patients with Lumbar Disc Prolapse Treated with Caudal Epidural Steroid Injections (Journal of Pakistan Orthopaedic Association, 2014)
Background: Sciatica is characterised by radiating pain in an area of leg typically served by one nerve root in sacral or lumbar spine. Majority of patients have herniated disc at a single level either at L4-5 or L5-S1. Epidural steroid injection is a low risk alternative as compared to surgical intervention in patients in whom conservative treatment has failed.Objectives: To determine the improved functional outcome in patients with lumbar disc prolapse treated with caudal epidural steroid injections.Subjects & Methods: After informed consent, using purposive non-probability sampling, fifty patients of either sex with ageranging from 20 to 50 years with MRI proven lumbar disc prolapse and having radicular pain were included. All patients were given caudal epidural steroid injection which included (triamcinolone) 80mg and long acting anesthetic agent (bupicaine)Results: Most of the patients were found with the age between 41-50 years i.e. 56%(n=28) mean and standard deviation was recorded as 38.64+7.99, male dominancy was observed in the study as 78%(n=39) were found as male. at final follow up i.e. 12th week, 4%(n=2) patients were found with poor results, 28%(n=14) had fair, 48%(n=24) had good and 20%(n=10) had excellent results.Conclusion: Improved functional outcome in patients with lumbar disc prolapse treated with caudal epidural steroid injections was found in the study.Key words: Disc prolapse, caudal epidural steroid injections, improved functional outcome